Aspek Hukum Perikatan dalam Kontrak Internasional : Perbandingan antara Hukum Indonesia dan Hukum Internasional - Aura Khairrun Nissa; Evan Azel Sutjipto; Indi Zahratul Ihsani (Letterlijk, 2024)
An internationalcontractis a contract that contains foreign elements and involves parties from various countries. In international contracts, there are differences in systems, paradigms and legal rules that apply in each country, so that legal harmonization and unification is needed to guarante ecertainty and security in international business transactions. International contracts in accordance with regulations regarding water pollution in Indonesia refer to Law Number 24 of 2000 concerning International Agreements. Settlement of national and international civil contract disputes more often uses the alternative of arbitration. This research analyzes the comparison between national contract law and international contracts. Dispute resolution in Indonesia is managed by BANI (Indonesian National Arbitration Board). To answer this problem, this research uses normative legal research methods. This writing uses an approachusing document study techniques, as well as study analysis using qualitative analysis.